(untitled) (Perner’s Contacts, 2011)
The article follows the author’s previous articles Analyze of transport organizing during public mass events in Hradec Králové and Examples of transport organizing during the public mass events published in Perner’s Contacts in years 2010 and 2011. In the paper is designed methodology of public transport organizing during public mass events by carrier and a detailed description of its individual steps.